Value-driven product service systems development: Methods and industrial applications. (November 2016) - Bertoni, Alessandro; Bertoni, Marco; Panarotto, Massimo; Johansson, Christian; Larsson, Tobias C.
Abstract: In recent times a service-dominant logic is permeating the design of complex systems. However, in spite of their appeal, initiatives such as Product Service Systems (PSS) have not become mainstream, and methods are lacking to support this transition. This paper argues that methodological guidance, as well as tools for decision support, may be found in the research field of Value Driven Design (VDD), which originates in the realm of Systems Engineering. The paper objective is to elaborate on gaps and opportunities for cross-pollination between VDD and PSS. The results of a systematic review of methods and tools for design decision support highlight the opportunity for introducing optimization models derived from VDD in the PSS design process, while the latter can enrich VDD research with a more qualitative value assessment logic. The paper summarizes this integration in a methodological approach, and exemplifies its application in case studies mainly from the aerospace and road construction equipment sector.